Motivation to Seek Knowledge from the Perspective of the Prophet's Hadith and Its Implications for Education - Mohammad Fattah; Inas Majidah (Penerbit Hellow Pustaka, 2026)
This study aims to examine the motivation to seek knowledge from the perspective of the hadith of the Prophet Muhammad (peace be upon him) and its implications for Islamic education. This study uses a qualitative approach with a library research method through analysis of various literature sources including the Qur'an, hadith, scientific books, and relevant journal articles. The results of the study indicate that knowledge in Islam originates from Allah SWT and has intellectual and spiritual dimensions. The Prophet's hadith emphasizes that seeking knowledge is an obligation for every Muslim regardless of gender, so that the activity of seeking knowledge has the value of worship and becomes a source of learning motivation. The implications of this study indicate that Islamic education needs to instill learning motivation oriented towards moral, spiritual, and social responsibility values in order to achieve comprehensive educational goals.